The ruff of equatorial emission around the SS433 jets: its spectral index and origin - Blundell, K; Rupen, M; Mioduszewski, A; Muxlow, T; Podsiadlowski, P (Center for Space Physics, 2003)
We present unique radio observations of SS433, using MERLIN, the VLBA, and the VLA, which allow us to, for the first time, properly image and derive a meaningful spectral index for the `ruff' of equatorial emission which surrounds SS433's jet. We interpret this smooth ruff as a wind-like outflow from the binary.